2016
DOI: 10.1177/2374373516667004
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Strategies for Engaging Families of Older Immigrants Hospitalized for End-of-Life Care

Abstract: Background:Engaging with families of older non-English-speaking background (NESB) immigrants hospitalized for end-of-life (EOL) care can be challenging, especially when their cultures, lifeways, and family decision-making processes are unfamiliar to the nurses caring for them. Despite the recognized importance of family engagement when providing EOL care, the issue of ethnic minority family engagement has received little attention in the field.Aim:To explore and describe the strategies nurses use to facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The differences between clinician communication roles at the end-of-life are presented in this systematic review and other studies. 36,37 Nurses assumed the role of the support person in communication at the end-of-life. This role included prompting physicians to have conversations with families regarding prognosis, taking direction from physicians, and supporting the family with cultural and religious rituals, 36,38 such as accessing religious texts or arranging for patients from the Muslim faith to face in the direction of Mecca when they die.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences between clinician communication roles at the end-of-life are presented in this systematic review and other studies. 36,37 Nurses assumed the role of the support person in communication at the end-of-life. This role included prompting physicians to have conversations with families regarding prognosis, taking direction from physicians, and supporting the family with cultural and religious rituals, 36,38 such as accessing religious texts or arranging for patients from the Muslim faith to face in the direction of Mecca when they die.…”
Section: Discussionmentioning
confidence: 99%
“…There is scope to increase the capability and capacity of nurses to engage in culturally sensitive communication at the end-oflife. 37 For this to occur, education should be a priority; however, to date, opportunities for clinicians to undertake education in culturally sensitive communication are rarely available, 45 such as teaching innovations described in literature on the topic area. 15 Multiple strategies to reduce challenges in communication with culturally diverse patients and families have been identified in this systematic review.…”
Section: Implications For Practicementioning
confidence: 99%
“…For older people with complex care needs who require hospitalisation, care may be provided in geriatric inpatient rehabilitation settings where multidisciplinary care is focused on optimising patient functioning (Australian Institute of Health & Welfare, 2013;Visser et al, 2014). Irrespective of the type of inpatient setting, hospitalisation is a highly stressful event for an older CALD person and their family, particularly as the older person approaches the end of life (Johnstone, Hutchinson, Rawson, & Redley, 2016). Significant disparities in end-of-life planning, decision making and care exist for older people from CALD backgrounds compared with those from mainstream English-speaking backgrounds (Betancourt et al, 2016;Johnstone & Kanitsaki, 2009).…”
Section: Summary Of Relevance Why Is This Research or Review Needed?mentioning
confidence: 99%
“…Yet, a recent review highlighted that the idea of what constitutes a good death varies considerably between and within cultures (Lloyd et al, 2011). Although clinicians can make a profound difference in how patients and their families experience and process patient death (Johnstone et al, 2016), recent evidence suggests that clinicians can feel overwhelmed and underprepared to provide end-of-life care (Bloomer et al, 2018 In Press) and not know how to initiate communication with patients and families about end-of-life care (Bloomer et al, 2018 In Press;Periyakoil et al, 2016). Another study found that nurses had little knowledge or understanding of what constituted culturally responsive or appropriate end-of-life care (Johnstone, Hutchinson, & Redley, 2015).…”
Section: Summary Of Relevance Why Is This Research or Review Needed?mentioning
confidence: 99%
“…Watson argued that self-awareness is unequivocally vital in nursing care, such that nurses are better equipped to practice sensitivity for others and their needs if they recognize their own feelings and emotions (Watson, 2007). The concept of sensitivity in EOL decision-making is akin to cultural or religious sensitivity when acknowledging that a patient's cultural or religious needs might dictate some aspects of their EOL preferences (Johnstone, Hutchinson, Rawson, & Redley, 2016).…”
Section: End Of Life Decision-making: Theory Of Human Caringmentioning
confidence: 99%